Optimization of the Agus Sastrawan Noor Library in Supporting Historical Studies For History Education Students At Tanjungpura University - Karomah; Atiqa Nur Latifa Hanum; Amriani Amir (UIN Raden Intan Lampung, 2026)
Abstract The Agus Sastrawan Noor Library is a specialized library inaugurated on January 29, 2024, to support the academic needs of History Education students. This study aims to analyze the library's role in developing historical studies for students and to identify the factors affecting its effectiveness. A descriptive qualitative method was employed using thematic analysis techniques. Data were collected through field observations, documentation studies (including collection statistical reports in SliMS), and semi-structured interviews with 3 informants, consisting of the head of the student library division, final-year students, and active students. The results indicate that the library functions as a source of information (providing national and local history book collections), a support for independent learning, and a space for intellectual interaction. Empirically, there are 1,183 book titles, with 78% already recorded in the system, while 22% remain undocumented. The thematic analysis findings identified the primary constraints: (1) limited collection of local history and access to academic journals; (2) the absence of a digital catalog system (OPAC) and systematic shelf labeling; and (3) circulation policies that do not yet permit the borrowing of collections due to their status as grants. This study recommends that the management: (1) digitize the collection and implement an OPAC system; (2) complete the collection of scientific journals and primary archives; and (3) optimize the use of the reading room as a forum for routine academic discussions to enhance information literacy and students' critical thinking skills. Keywords: special library; historical studies; higher education;